PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, DISIPLIN KERJA, IKLIM KERJA, DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI SMK NU LASEM - Irshandy, Dodi; Ilhami, Susanti Dwi (STKIP Pesisir Selatan, 2025)
This study aims to examine and analyze the influence of School principal leadership, work discipline, work climate, and work motivation on teacher performance at SMK NU Lasem. The research employs a quantitative approach using a survey method, in which all 48 teachers were included as the sample through a total sampling technique. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression using SPSS version 25. The results of the study indicate that work discipline, work climate, and work motivation have a positive and significant effect on teacher performance, while principal leadership has a negative but insignificant effect. The determination test shows that the four independent variables together are able to explain the variation in changes in teacher performance by 69.4%, while the remaining 30.6% is influenced by other factors outside this study. These results confirm that high work discipline, a good work climate, and strong motivation are the keys to improving teacher performance in vocational school environments.